Hypotensive effect of Eugenia dysenterica leaf extract is primarily related to its vascular action: The possible underlying mechanisms - Fidelis-de-Oliveira, Patrícia [UNESP]; Aparecida-Castro, Samanta [UNESP]; Silva, Denise Brentan; Morais, Ingrid Beatriz de Melo; Miranda, Victor Hugo Martins de [UNESP]; de Gobbi, Juliana Irani [UNESP]; Canabrava, Hudson Armando Nunes; Bispo-da-Silva, Luiz Borges (Elsevier, 2020)
Ethnopharmacological relevance: Eugenia dysenterica (ED) leaves are used in Brazil to treat cardiac diseases; however, there are no scientific data describing the effects of this species on cardiac activity. Aim of the study: To investigate the effect of ED aqueous leaf extract (EDLE) on hear rate (HR) and mean arterial pressure (MAP) of anaesthetised rats and its underlying mechanism of action. Material and methods: EDLE was analysed, and its proanthocyanidin composition was determined. After performing dose-effect curves for EDLE on HR and MAP, EDLE-induced hypotension was evaluated before and after atropine (AT), L-N(ω)-nitro-L-arginine methyl ester (L-NAME), hexamethonium (HXT), indomethacin (IND), carbenoxolone (CBX), or nifedipine (NFD) administration. The effect of proanthocyanidin-depleted extract (EDLE/P-) was also determined and compared to that of the EDLE with proanthocyanidins. Results: EDLE decreased the MAP in a dose-dependent manner; HR was decreased only with the highest and most toxic dose. Only CBX and NFD decreased EDLE-induced hypotension. Five polymeric series of proanthocyanidins were identified, which were mainly constituted by procyanidin and prodelphinidin units with B-type linkage and up to 12 flavan-3-ol units. EDLE/P- induced hypotension did not differ from that induced by EDLE. Conclusions: The cardiovascular effects of EDLE were primarily related to its vascular action. EDLE-induced hypotensive effect appeared to involve L-type calcium channel blockage as well as myoendothelial gap junction signalling. The higher molecular weight proanthocyanidins from EDLE are unlikely to contribute to its cardiovascular effect.
Keywords: Eugenia dysenterica; Heart; Hypotension; Leaves; MALDI-TOF; Proanthocyanidins